SOAL MODEL PISA KONTEN SPACE & SHAPE UNTUK MENUNJANG KEMAMPUAN BERPIKIR MATEMATIS PESERTA DIDIK - Satiti, Wisnu Siwi; Lathifah, Afifatul; Nasrulloh, M Farid (Universitas KH. A. Wahab Hasbullah, 2021)
In order to develop students' mathematical abilities, a learning should not only emphasize mastery of the material, but mathematical activities should also support the development of students' ability to think mathematically. This due to mathematical thinking is important for a student's academic success and is also an ability needed in the role of each individual in society. One of the mathematical activities that support students' mathematical thinking skills is PISA like mathematics problems. One of the mathematical content in PISA is about space and shape. However, several previous studies have shown that many Indonesian students have difficulty in solving PISA like mathematics problems of space and shape content Therefore, in this study, PISA like mathematics problems of space and shape content was developed for students at the SMP/MTs level. The product is used as a mathematical activity in learning at school as an effort to support students' mathematical thinking. This study uses the Research and Development (R&D) method with the ADDIE model. The product trial results show that the product developed is valid and appropriate to support students' mathematical thinking. The final product received a response with